AKIDAH AKHLAK DALAM PENDIDIKAN AGAMA ISLAM: KAJIAN TERHADAP PERAN MORAL DALAM PEMBENTUKAN KARAKTER PELAJAR - Jusmaliah, Jusmaliah; Risnawati Hannang; Nurul Ilma (Indonesian Journal of Islamic Studies (IJIS), 2025)
Islamic Religious Education (PAI) plays a critical role in shaping both the intellectual and moral character of students. It emphasizes the importance of akidah (faith) and akhlak (ethics) as the core elements of Islamic teachings. Akidah involves a profound belief in the One and Only God, Allah SWT, while akhlak reflects a person’s behavior towards God and fellow human beings. Education focused on these aspects helps create well-rounded students who possess not only intellectual capabilities but also strong moral values, empathy, and the ability to contribute positively to society. However, the rise of globalization and technological advancements, particularly through social media, presents challenges in preserving Islamic values in education. These external influences can expose students to ideologies and behaviors that conflict with Islamic principles. Historical Islamic figures, including the Prophets, have exemplified the correct practice of akidah and akhlak, setting an example for current generations. The Quran and Hadith emphasize the importance of adhering to moral values and avoiding negative behaviors. As such, integrating akidah and akhlak in the PAI curriculum is vital for developing students' character and integrity. This study aims to explore how moral education can shape the character of students by focusing on akidah and akhlak, and how this integration can create a generation that is responsible, principled, and capable of thriving in a complex and diverse world. By enhancing akidah and akhlak education, this study seeks to contribute to the improvement of educational policies and the development of morally grounded individuals in Indonesian society.